2013
DOI: 10.1179/2049396713y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and longitudinal analysis of health impacts and stressors perceived to result from unconventional shale gas development in the Marcellus Shale region

Abstract: Exposure-based epidemiological studies are needed to address identified health impacts and those that may develop as unconventional natural gas extraction continues. Many of the stressors can be addressed immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 18 publications
2
88
0
Order By: Relevance
“…Similarly, researchers have reported that higher levels of stress in these areas are linked to an individual's belief that their health has been affected (Ferrar et al, 2013). Higher scores on the DASS-21 for participants in the CSG area would support this hypothesis.…”
Section: Discussion Of Depression Anxiety and Stress (Dass-21 Outcosupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly, researchers have reported that higher levels of stress in these areas are linked to an individual's belief that their health has been affected (Ferrar et al, 2013). Higher scores on the DASS-21 for participants in the CSG area would support this hypothesis.…”
Section: Discussion Of Depression Anxiety and Stress (Dass-21 Outcosupporting
confidence: 61%
“…As previously mentioned, the expansion of UNGD has caused community residents, as well as medical and public health professionals, to voice concerns about the environmentally-related health impacts of natural gas (Ferrar et al, 2013;McDermott-Levy, Kaktins, & Sattler, 2013;McKenzie, Witter, Newman, & Adgate, 2012;Queensland Government, 2013d While a number of studies call for more research into the potential for adverse health outcomes associated with UNGD, there appears to be a dearth of reporting on this issue in the literature. More specifically, there are significantly fewer studies specific to CSG than to other unconventional gas resources; hence, the need to expand the review to the broader category of UNGD.…”
Section: Primary Environmental Setting: Erhis Related To Csgmentioning
confidence: 97%
See 1 more Smart Citation
“…Faculty at CHEC enlisted a small group of graduate students eager to engage with health issues related to drilling in the Marcellus Shale region of Pennsylvania. Their projects covered various aspects of the industry, including visually documenting impacts, air and water quality monitoring, and public health surveys (Ferrar, Kriesky, et al 2013;). The FracTracker.org blog was used to contextualize CHEC research with drilling maps and data analysis.…”
Section: Filling Data Gaps: Fractracker Alliancementioning
confidence: 99%
“…Among the more common self-reported symptoms are fatigue, irritation of the upper respiratory tract, burning eyes and shortness of breath. 10,11 However, there are no formal epidemiologic studies or health impact assessments that support or refute these observations, or that consider vulnerable populations. [1][2][3][4] Physicians should be aware of the sources of confusion over fracking that have contributed to public distrust and the social amplification of risk.…”
mentioning
confidence: 99%